2012
DOI: 10.1007/978-1-62703-125-7_2
|View full text |Cite
|
Sign up to set email alerts
|

Culture of Choroid Plexus Epithelial Cells and In Vitro Model of Blood–CSF Barrier

Abstract: Chemical homeostasis in the extracellular fluid of the central nervous system (CNS) is maintained by two brain barrier systems, i.e., the blood–brain barrier (BBB) that separates the blood circulation from brain interstitial fluid and the blood–cerebrospinal fluid barrier (BCB) that separates the blood from the cerebrospinal fluid (CSF). The choroid plexus, where the BCB is located, is a polarized tissue, with the basolateral side of the choroidal epithelium facing the blood and the apical microvilli in direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 24 publications
2
43
0
1
Order By: Relevance
“…Recent advances in the generation of an immortalized choroid plexus cell line for use in in vitro experiments may prove extremely valuable in efforts to understand Na,K-ATPase trafficking in this tissue. 127 In the case of RPE cells, the absence of epithelial-specific m1B AP expression is associated with the aberrant apical localization of the coxsackie and adenovirus receptor protein. 128 Interestingly, knockdown experiments in MDCK cells demonstrated that m1B is required for correct recycling of coxsackie and adenovirus receptor to the basolateral membrane, but not for its initial biosynthetic delivery.…”
Section: Cell-specific Variations In Traffickingmentioning
confidence: 41%
“…Recent advances in the generation of an immortalized choroid plexus cell line for use in in vitro experiments may prove extremely valuable in efforts to understand Na,K-ATPase trafficking in this tissue. 127 In the case of RPE cells, the absence of epithelial-specific m1B AP expression is associated with the aberrant apical localization of the coxsackie and adenovirus receptor protein. 128 Interestingly, knockdown experiments in MDCK cells demonstrated that m1B is required for correct recycling of coxsackie and adenovirus receptor to the basolateral membrane, but not for its initial biosynthetic delivery.…”
Section: Cell-specific Variations In Traffickingmentioning
confidence: 41%
“…Primary cultures of mouse astrocytes and choroid plexus epithelial cells were performed, as reported [40, 48]. In brief, the choroid plexus from the lateral ventricles and 4 th ventricle were removed from 15 C57BL6 male mice (4–8 weeks old), digested in 0.4% pronase in Hank’s balanced salt solution (HBSS) and cultured in Dulbecco’s modified Eagle’s medium (DMEM) containing fetal bovine serum (FBS), epidermal growth factor (EGF) and antibiotics (penicillin/streptomycin) on collagen coated wells.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, Z310 cells have the same polygonal morphology of CP epithelial cells, forming confluent monolayers as the primary cell cultures. The cell line Z310 was cultured as described previously [67].…”
Section: Cell Culture and Sirna Knockdownsupporting
confidence: 48%